Electrical and optical properties of aluminium doped zinc oxide transparent conducting oxide films prepared by dip coating technique. Issue 1 (3rd January 2017) - Manjakkal, Libu; Packia Selvam, I.; Potty, S.N.; Shinde, R.S.
Abstract : Purpose: Aluminium-doped zinc oxide thin films exhibit interesting optoelectronic properties, which make them suitable for fabrication of photovoltaic cell, flat panel display electrode, etc. It has been shown that aluminium dopant concentration and annealing treatment in reduced atmosphere are the major factors affecting the electrical and optical properties of aluminium doped zinc oxide (AZO) film. Here, the authors report the structural, optical and electrical properties of aluminium-doped zinc oxide thin films fabricated by dip coating technique and annealed in air atmosphere, thereby avoiding hazardous environments such as hydrogen. The aim of this paper was to systematically investigate the effect of annealing temperature on the electrical properties of dip-coated film. Design/methodology/approach: Aluminium-doped ZnO thin films were prepared on corning substrates by dip coating method. Aluminium concentration in the film varied from 0.8 to 1.4 mol per cent. Films have been characterized by X-ray diffraction, scanning electron microscopy, atomic force microscopy, UV-visible spectroscopy and Hall measurements. The deposited films were heat treated at 450-600°C, in steps of 50°C for 1 h in air to study the improvement in electrical properties. Films were also prepared by annealing at 600°C in air for durations of 1, 2, 4 and 6 h. Envelope method was used to calculate the variation of the refractive index and extinction coefficient with wavelength. Findings: The electrical resistivity is found to decrease considerably when the annealing time is increased from 1 to 4 h. The films exhibited high transmittance (>90 per cent) in the visible range, and the optical band gaps were found to change as per the Moss–Burstien effect, and this was consistent with the observed changes in the carrier concentration. Originality/value: The study shows the effect of annealing in air, avoiding hazardous reduced environment, such as hydrogen, to study the improvement in electrical and optical properties of aluminum-doped zinc oxide films. Envelope method was used to calculate the variation of optical constants with wavelength.